THE EFFECT OF PRODUCT QUALITY, AND BRAND IMAGES ON PURCHASING DECISIONS THROUGH THE ROLE OF PURCHASE INTENTION AS AN INTERVENING VARIABLE - Lukitaningsih, Ambar; Cahya, Agus Dwi; Mizan, Dwi Iskandar (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research is quantitative research, which was conducted to test the influence of product quality, brand image, and purchase intention as intervening variables on purchasing decisions. The data in this research was collected through a questionnaire using Google form with respondents who were owners, users, or who had purchased an iPhone brand smartphone in Yogyakarta. The sample taken in this research was 115 people. Sampling was carried out using a non-probability sampling method and using a purposive sampling technique. For data processing, use SPSS version 22. The results of this research show that product quality, brand images, purchase intention have a positive and significant effect on purchasing decisions.